PENERAPAN MODEL PEMBELAJARAN SNOWBALL TROWING UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS V SD NEGERI 0126 LEMBAH BINUBU - Nur Khadijah Pulungan; Nurhayati Siregar; Rizki Hamdan Saputra (CV. ADIBA ASIHA AMIRA, 2023)
The importance of planned educational programs that make students active in the learning process, only through the involvement or activeness of students in the learning process are they able to develop their potential and creativity in learning. This study uses a class action research method (CAR). Data collection techniques in this study were obtained through observation, documentation and tests. And data analysis techniques in this study using qualitative and quantitative analysis. Based on the results of the actions that have been taken by the researchers, it can be concluded that through the application of the snowball trowing learning model it can create an active class situation, students dare to express opinions, work together, use analytical abilities, and move actively during the learning process. The use of the snowball throwing learning model can also train students' readiness and impart knowledge to each other.